Somewhere today - Kitchen, Bert. (Cambridge, Mass. : Candlewick Press, 1992)
Describes unusual animal rituals of work, play, courtship, and survival.
Children's Catalog (Wilson)
School Library Journal
Publisher's Weekly
6.8
3-6
Keywords: Animal behavior -- Juvenile literature; Animals -- Habits and behavior; Animals -- Behavior